MANAGEMENT OF CHEMICAL AND MICROBIOLOGICAL WATER QUALITY IN POOLS FOR SWIMMING AND RECREATION - Antonić, B.; Gligorić, M.; Došić, A.; Vujadinović, D.; Grujić, R.; Babić, D. (Journal of Engineering & Processing Management, 2016)
Use of water for recreation or treatment of very it’s very important to maintain health and working capacity of the population. A significant number of people temporarily or permanently, used pools for that purpose. That is why today, in the developed countries, great attention is paid to the quality of water for recreation. The aim of this work is to manage pools in terms of managing chemical and microbiological quality of water. Consideration of the problem of managing chemical microbiological quality of water in swimming pools is based on the relevant Recommendations of the World Health Organization. Retrospective-descriptive method is used to analyze the results of laboratory tests of swimming pool water in the city of Banja Luka in 2013 and 2014. Results of the analysis showed that the physical and chemical inadequacy of water is mainly related to increased chloride content in water, while microbiologically defectives are caused by the increased number of coliform bacteria.